Statins-Beyond Their Use in Hypercholesterolemia: Focus on the Pediatric Population - Elena Lia Spoiala; Eliza Cinteza; Radu Vatasescu; Mihaela Victoria Vlaiculescu; Stefana Maria Moisa (MDPI AG, 2024)
Statins are a class of medications primarily used in adults to lower cholesterol levels and reduce the risk of cardiovascular events. However, the use of statins in children is generally limited and carefully considered despite the well-documented anti-inflammatory, anti-angiogenic, and pro-apoptotic effects, as well as their effect on cell signaling pathways. These multifaceted effects, known as pleiotropic effects, encompass enhancements in endothelial function, a significant reduction in oxidative stress, the stabilization of atherosclerotic plaques, immunomodulation, the inhibition of vascular smooth muscle proliferation, an influence on bone metabolism, anti-inflammatory properties, antithrombotic effects, and a diminished risk of dementia. In children, recent research revealed promising perspectives on the use of statins in various conditions including neurological, cardiovascular, and oncologic diseases, as well as special situations, such as transplanted children. The long-term safety and efficacy of statins in children are still subjects of ongoing research, and healthcare providers carefully assess the individual risk factors and benefits before prescribing these medications to pediatric patients. The use of statins in children is generally less common than in adults, and it requires close monitoring and supervision by healthcare professionals. Further research is needed to fully assess the pleiotropic effects of statins in the pediatric population.